PC3 - 154 Phase I/II Study of VAL-083 in Patients with Recurrent Glioblastoma. (18th October 2016) - Shih, K.C.; Patel, M.R.; Butowski, N.; Falchook, G.S.; Kizilbash, S.H.; Bacha, J.A.; Brown, D.M.; Steino, A.; Schwartz, R.; Kanekal, S.; Lopez, L.M.; Burris, H.A.
Abstract : Glioblastoma (GBM) is the most common brain cancer. Resistance to front-line systemic therapy with temozolomide (TMZ) is correlated with O6-methylguanine-DNA-methyltransferase (MGMT) expression. Second-line treatment with bevacizumab has not improved overall survival. Dianhydrogalactitol (VAL-083) is a bi-functional alkylating agent that has MGMT-independent cell-kill activity against GBM cell-lines and cancer stem cells in vitro. VAL-083 crosses the blood-brain barrier and showed promise against CNS tumors in prior NCI-sponsored clinical trials. The goal of this clinical trial is to determine appropriate VAL-083 dosing for advancement to Phase III trials as a new treatment for recurrent GBM. METHODS: Patients must have recurrent GBM following surgery, radiation, TMZ and bevacizumab. Phase I: Open-label, single-arm, dose-escalation study. Patients received VAL-083 on days 1, 2, 3 of a 21-day cycle, until reaching MTD. Phase II: Additional patients enrolled at MTD to further assess safety and outcomes. RESULTS: Phase I: 29 patients were enrolled across 9 dose cohorts (1.5-50 mg/m2/d). 40mg/m2/d was confirmed as MTD. Myelosuppression was mild; no drug-related serious adverse events were reported at doses up to 40mg/m2/d. Dose limiting G4 thrombocytopenia was observed at higher doses. Platelet nadir occurred around day 20 and resolved rapidly and spontaneously. A dose-related survival improvement was observed. Pharmacokinetic analyses show 1-2h plasma terminal half-life; average Cmax 781ng/mL at 40mg/m2/d. Phase II: 14 patients were enrolled at 40mg/m2/d. To date, safety observations in Phase II are consistent with Phase I. CONCLUSIONS: VAL-083 at 40mg/m2/d exhibits a favorable safety profile and dose-related trend toward clinically meaningful improved survival in refractory GBM patient